Jiangyiqi attitude: an exploratory research into its measure and examination of construct validity. (16th June 2022) - Wei, Wu; Liang, Xin; Lu, Feng; Wang, Jianyou; Ren, Yufei
In this paper we report an exploratory empirical research of a novel construct, Jiangyiqi, which was recently introduced by Liang et al. (2018) into the literature on management and relationship development in Chinese culture. Defined as a special type of Bao attitude under adverse situations, Jiangyiqi concept bridges a gap addressing when reciprocal favour exchange may fail and when it may sustain. An eight-item, three component structure measures is supported by data collected from 156 undergraduate students and 150 store managers in an international fast food company. Convergent validity was also checked through the significance covariance that these three factors have with a direct, overall measure of individual's Jiangyiqi attitude, as well as through a second order confirmatory factor analysis. An acceptable level of convergent validity was achieved. It was also found that the cognitive component has a weak connection with latent Jiangyiqi attitude variable, while affective and behavioural components are strong indicators of Jiangyiqi.